Chapter 16. Increasing adaptation to climate stress by applying conservation agriculture in Southern Africa - Thierfelder, Christian L.; Steward, Peter R. (CAB International, 2022)
Climate change and soil fertility decline are threatening food security in southern Africa and efforts have been made to adapt current cropping systems to the needs of smallholder farmers. Conservation Agriculture (CA) based on minimum soil disturbance, crop residue retention and crop diversification has been proposed as a strategy to address the challenges smallholder farmers face. Here we analyse the potential contributions of CA towards adaptation to the effects of climate change by summarizing data on infiltration, soil moisture dynamics and crop productivity under heat and drought stress. The data were taken in the main from CIMMYT’s on-farm and on-station trial network. Data show that CA systems maintain 0.7-7.9 times higher water infiltration than the conventional tilled system depending on soil type, which increases soil moisture during the cropping season by 11%-31% between CA treatments and the conventional control treatment. This leads to greater adaptive capacity of CA systems during in-season dry spells and under heat stress. A supporting regional maize productivity assessment, analysing the results of numerous on-farm and on-station experiments, showed that CA systems will outperform conventional tillage practices (CP), especially on light-textured soils, under heat and drought stress. With higher rainfall and low heat stress, this relation was more positive towards CP and on clay soil there was no benefit of practising CA when rainfall was high. The long dry season and limited biomass production of CA systems in southern Africa require complementary good agricultural practices to increase other soil quality parameters (e.g. increased soil carbon) to maintain higher productivity and sustainability over time. This can be addressed by combinations of improved stress-tolerant seed, targeted fertilization, inclusion of tree-based components or green manure cover crops in the farming system, scale-appropriate mechanization and improved weed control strategies.